1999
DOI: 10.2337/diacare.22.11.1875
|View full text |Cite
|
Sign up to set email alerts
|

Sex hormone-binding globulin levels in middle-aged premenopausal women. Associations with visceral obesity and metabolic profile.

Abstract: Our results suggest that the previously reported relationship between low SHBG levels and increased metabolic disease risk in women is mediated, to a large extent, by concomitant variation in body fatness and intra-abdominal adipose tissue accumulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
53
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 0 publications
9
53
0
Order By: Relevance
“…Means 6 SD were reported for 66 subjects (36 white and 30 black women). Values for SHBG and TT were similar to other studies and within normal range (14,15). Figure 1 presents the relationship between two different measures of central obesity, SAT and VAT, with metabolic variables associated with CVD risk.…”
Section: Physical Characteristicssupporting
confidence: 54%
See 1 more Smart Citation
“…Means 6 SD were reported for 66 subjects (36 white and 30 black women). Values for SHBG and TT were similar to other studies and within normal range (14,15). Figure 1 presents the relationship between two different measures of central obesity, SAT and VAT, with metabolic variables associated with CVD risk.…”
Section: Physical Characteristicssupporting
confidence: 54%
“…Studies have already shown that elevated androgens and low SHBG are related to metabolic variables associated with CVD risk (11)(12)(13). However, some studies have shown that upon controlling for VAT, the relationship between metabolic variables and SHBG and/or bioavailable testosterone is no longer found (14)(15)(16). Furthermore, others have postulated that it is the bioavailable testosterone that regulates VAT accumulation associated with CVD risk, and may even directly contribute to CVD risk (10,17).…”
Section: Introductionmentioning
confidence: 99%
“…These women also have higher androgen activity (as reflected by the testosteroneto-SHBG ratio) than postmenopausal women with NGT (32). Because insulin inhibits SHBG secretion in the liver (33), the hyperinsulinemic state of women with IGT may be associated with a dyslipidemic profile through alterations in SHBG and the estrogen/androgen balance (34).…”
Section: Results -mentioning
confidence: 99%
“…26 On the other hand, low SHBG and high estrogen levels are associated with increased total and central adiposity in women. 20,[27][28][29] SHBG is a protein that binds primarily to steroids such as estrogen. As only the unbound steroid fraction is biologically active, SHBG may play an important role in both AAM and obesity through determining the amount of free estrogen.…”
Section: Discussionmentioning
confidence: 99%